Heat shock activation of the groESL operon of Agrobacterium tumefaciens and the regulatory roles of the inverted repeat. - Segal, G (1996)
Deletions were constructed in the conserved inverted repeat (IR) found in the groESL operon of Agrobacterium tumefaciens and in many other groE and dnaK operons and genes in eubacteria. These deletions affected the level of expression of the operon and the magnitude of its heat shock activation. The IR seems to operate at the DNA level, probably as an operator site that binds a repressor under non-heat shock conditions. The IR was also found to function at the mRNA level, since under non-heat shock conditions transcripts containing deletions of one side of the IR had longer half-lives than did transcripts containing the wild-type IR. Under heat shock conditions, the half-life of the mRNA was unaffected by this deletion because of heat shock-dependent cleavage. However, the groESL operon was found to be heat shock activated even after most of the IR was deleted. This observation, together with the fact that the groESL operon of A. tumefaciens was heat shock activated in Escherichia coli and vice versa, suggests that a heat shock promoter regulates the heat shock activation of this operon. The primary role of the IR appears to be in reducing the MRNA levels from this promoter under non-heat shock conditions.